Conquer synthesis and transformation for primary levels 1: 600 creative and varied questions - Lee, J. (Singapore, 2007)
The Book exercises are organized thematically such that the use of a connecting word is enforced over a few exercises. An example is provided at the start of each exercise as a guide for students. Revision exercises are included for extra practice. Answers are provided for easy self-assessment. The pages of the book are perforated so that each exercise can be easily detached and used as a worksheet for classroom and/or home learning.
Keywords: English Language Grammar